A Pragmatic Analysis of Persuasive Language in Children-Oriented Discourse: The Case of Smash Boom Best Podcast - Reva Nur Alfiany; Pepen Priyawan; Erlan Aditya Ardiansyah (Journal of English Language and Education, 2026)
This study investigates persuasive language strategies employed in children-oriented debate discourse by analyzing the Smash Boom Best episode “Forts vs. Puzzles”. The episode was selected because it features a structured debate between two adult speakers evaluated by a child judge, providing a rich context for examining audience-oriented persuasive discourse. This study aims to identify persuasive strategies and explain their pragmatic functions. A descriptive qualitative approach was employed using spoken utterances manually transcribed from the podcast episode published on the official Brains On! YouTube channel. The data were analyzed through qualitative content analysis using Leech's pragmatic framework and Aristotelian rhetoric. The findings reveal that pathos is the dominant persuasive strategy often realized through improvisational narrative and humor supported by logos, audience adaptation, and opponent-weakening strategies. These findings demonstrate how rhetorical appeals and pragmatic adaptation work together to engage child audiences, contributing to the understanding of persuasive discourse in children's digital audio media.